2015
DOI: 10.1111/isj.12071
|View full text |Cite
|
Sign up to set email alerts
|

Towards an understanding of the role of business intelligence systems in organisational knowing

Abstract: Recent advances in information technology (IT), such as the advent of business intelligence (BI) systems, have increased the ability of organisations to collect and analyse data to support decisions. There is little focus to date, however, on how BI systems might play a role in organisational knowledge creation -in organisational knowing. We develop a conceptual framework of organisational knowing based on a synthesis of the literature, and use this as a framework to investigate how BI systems facilitate knowi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
97
0
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(110 citation statements)
references
References 72 publications
0
97
0
7
Order By: Relevance
“…Third, technology is not able to substitute human interactions, meetings and dialogue (Prieto & Easterby-Smith, 2006), and more recent studies assert that KMS cannot successfully enhance knowledge sharing without taking social and organisational aspects into account (Padova & Scarso, 2012). This limitation is even more strongly recognised from the practice-based perspective where KS is seen to be driven by social interactions (Newell & Galliers, 2006;Shollo & Galliers, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, technology is not able to substitute human interactions, meetings and dialogue (Prieto & Easterby-Smith, 2006), and more recent studies assert that KMS cannot successfully enhance knowledge sharing without taking social and organisational aspects into account (Padova & Scarso, 2012). This limitation is even more strongly recognised from the practice-based perspective where KS is seen to be driven by social interactions (Newell & Galliers, 2006;Shollo & Galliers, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…More recent studies suggest that such knowledge sharing could be supported with the use of interactive Web 2.0 tools (Wagner & Bolloju, 2005;Davison et al, 2013;Von Krogh, 2012), whose socially-driven and interactive features help overcome the limitations of the traditional ICT used in organisations (Kaiser et al, 2007;McAfee, 2006), and whose role is to facilitate action (Shollo & Galliers, 2016). However, the effect of Web 2.0 technologies on knowledge processes, and the impact of their implementation in organisations, are under-explored in IS research (Huang et al, 2015;Von Krogh, 2012).…”
mentioning
confidence: 99%
“…Through the successful use of Business Intelligence and Analytics (BI&A), organisations can harvest and extract greater value from their data assets, thus more likely able to outperform their competitors (LaValle, Lesser, Shockley, Hopkins & Kruschwitz, 2011;Sidorova & Torres, 2015). Analysis of data through the use of BI&A tools and techniques allows organisations to gain insights into key areas to drive effective decision making (Chaudhuri, Dayal & Narasayya, 2011;Rouhani, Ashrafi, Zare & Afshari, 2016;Shollo & Galliers, 2015). LaValle et al (2011) concluded that higher performing organisations are twice as likely to use analytics whether it be for growth, efficiency or competitive advantage purposes.…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of data-driven decision making are both improved productivity and market value, as was empirically shown in a study by Brynjolfsson, Hitt and Kim (2011) who concluded that organisations who adopted data-driven decision-making practices showed 5-6% higher productivity rates. BI&A practices and tools are seen as key enablers of data-driven decision making and provide the framework and support for organisations wanting to make better fact-based decisions (Davenport & Dyché, 2013;Shollo & Galliers, 2015;Wixom & Watson, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Based on extensive literature reviews, several authors focus on understanding, conceptualization and/or systematization of BI, see for example [6], [8], [24], [34] and [35]. Frequently, BI is differentiated into BIas-product, BI-as-a-process and BI-as-a-tool.…”
Section: Bianda Historymentioning
confidence: 99%